Human Flourishing and History: A Religious Imaginary for the Anthropocene. - Tirosh-Samuelson, Hava (Journal of the Philosophy of History, 2020)
The Anthropocene denotes the impact of human activity on Earth systems, resulting in mass extinctions of plant and animal species, pollution of oceans, lakes and rivers, and altering of the atmosphere. The Anthropocene signifies the mass control of nature by humans, the erasure of boundaries between humanity and nature, and the threat to human existence by human-made technology. How can biological humans flourish, if their physical environment, the very condition of their existence, is destroyed? What does it mean to thrive as a human in an age when human-made machines threaten to make humanity obsolete? How does human flourishing relate to human history? This essay argues that the monotheistic traditions, and Judaism in particular, offer meaningful religious imaginaries for the Anthropocene because they envision human flourishing as embodied, ecological and historically grounded. In contrast to secular imaginaries, which either declare the "end of nature" or envision the obsolescence of biological humanity, the Judaic religious imaginary honors the interconnectedness and interdependence of all creatures, while recognizing human responsibility toward the well-being of the natural world. Viewing nature as divinely created, and, thus "enchanted" by the divine presence, the Judaic religious imaginary offers a vision of human flourishing based on the ethics of care and responsibility that enables humanity to respond and perhaps even prevent further ecological collapse.